Horizontal versus vertical force application: association with the change of direction performance in soccer players - Robles-Ruiz, J.; Baena-Raya, A.; Jiménez-Reyes, P.; Soriano-Maldonado, A.; Rodríguez-Pérez, M. A. (European Journal of Sport Science, 2023)
This study examined which mechanical variables derived from a vertical jump (i.e. concentric peak force [ConcPF] and eccentric peak force [EccPF], flight time [FT]: contraction time [CT], eccentric deceleration rate of force development [EccDecRFD]) and linear sprint (i.e. theoretical maximal force [F0] and velocity [V0], maximal power output [Pmax], the peak ratio of the effective horizontal component [RFpeak], and the index of force application technique [DRF]) determined the change of direction (COD) performance to a greater extent. Sixteen male soccer players (age: 21.8 ± 2.9 years; height: 175.94 ± 6.88 cm; weight: 73.23 ± 9.59 kg) were assessed for a countermovement jump, the horizontal force velocity (FV) profile, and the COD ZigZag test. The horizontal FV profile parameters were significantly associated with COD performance, while jump mechanical variables did not show any significant association (r = 0.08-0.19; p > 0.05). Specifically, F0 (r = -0.56), Pmax (r = -0.68), and RFpeak (r = -0.54) were strongly associated with COD performance. Moreover, a 1 N/kg increase in F0 was associated with -0.11 s to complete the ZigZag test, whereas 1 W/kg and 1% increase in Pmax and RFpeak were associated with -0.05 and -0.03 s, respectively, to complete the COD test. Horizontal force production during sprinting might play a key role in COD performance. Assessing the horizontal FV profile might help coaches to prescribe a specific training programme to maximize sprint acceleration, which might improve COD performance.